Nanomedicine-based strategies to target and modulate the tumor microenvironment - Mendes, Bárbara B. (2021)
Funding Information: The authors acknowledge financial support from Fundação para a Ciência e a Tecnologia / Ministério da Ciência, Tecnologia, e Ensino Superior in the framework of PhD grant 2020.06638.BD (to D.P.S.), and from the European Research Council grant agreement No 848325 (J.C. for the ERC Starting Grant). Funding Information: The authors acknowledge financial support from Funda??o para a Ci?ncia e a Tecnologia/ Minist?rio da Ci?ncia, Tecnologia, e Ensino Superior in the framework of PhD grant 2020.06638.BD (to D.P.S.), and from the European Research Council grant agreement No 848325 (J.C. for the ERC Starting Grant). None declared by authors. Publisher Copyright: © 2021 Elsevier Inc.